2018
DOI: 10.1177/0731684418799528
|View full text |Cite
|
Sign up to set email alerts
|

Tensile and flexural properties of natural fiber reinforced polymer composites: A review

Abstract: In recent years, researchers and scientists are facing problems in terms of environmental imbalance and global warming owing to numerous use of composite materials prepared by synthetic fibers and petrochemical polymers. Hence, an increasing attention has been devoted to the research and development of polymer composites reinforced with the natural fibers. The natural fibers are the most suitable alternative of synthetic fibers due to their biodegradability, eco-friendliness and acceptable mechanical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(72 citation statements)
references
References 106 publications
0
61
0
Order By: Relevance
“…The main limitation of natural fiber is its poor mechanical strength, poor dimension stability, high moisture absorption, high swelling, incompatibility with the hydrophobic polymer matrix, and low thermal resistance [34][35][36][37][38]. These limitations can be overcome by various chemical and physical treatments [39][40][41][42].…”
Section: Chemical Treatment Methodsmentioning
confidence: 99%
“…The main limitation of natural fiber is its poor mechanical strength, poor dimension stability, high moisture absorption, high swelling, incompatibility with the hydrophobic polymer matrix, and low thermal resistance [34][35][36][37][38]. These limitations can be overcome by various chemical and physical treatments [39][40][41][42].…”
Section: Chemical Treatment Methodsmentioning
confidence: 99%
“…The flexural test was performed at room temperature using the same model of the Instron machine. A crosshead displacement speed of 2 mm/min T A B L E 1 Compiled properties of kenaf and PALF [12,26]…”
Section: Mechanical Testmentioning
confidence: 99%
“…Natural fibre reinforced polymer composites (NFRCs) has become a popular choice to substitute the synthetic reinforcing fibre because of abundance in availability, a renewable resource, economic, low density, biodegradable and have good specific properties [1][2][3]. Khan et al [4] have shown that the NFRCs used in engineering applications such as in the automotive, aerospace, and construction industries. As reinforcement, it drives the natural fibre to be reused and recycled based on their specific mechanical properties.…”
Section: Introductionmentioning
confidence: 99%